Nandina domestica Thunb.: a review of traditional uses, phytochemistry, pharmacology, and toxicology - Qian, Huiqin; Li, Yanling (Frontiers in Pharmacology, 2024)
Nandina domestica Thunb. is a traditional Chinese herbal drug that has long been used in China and Japan for the treatment of colds, fevers, asthma, chronic bronchitis, conjunctivitis, whooping cough, pharyngeal tumors, etc. Published data have reported at least 366 constituents from N. domestica, including alkaloids, flavonoids, lignans, terpenoids, phenolic acids and their derivatives, fatty acids, and others. Of these, the isoquinoline alkaloids are considered characteristic markers for N. domestica. These alkaloids also showed the most promising bioactivities.The crude extracts or semi-purified constituents of N. domestica exhibit a variety of activities, including antitumor, dermatological, anti-inflammatory, antioxidant, antimicrobial, and detoxification activities, as well as effects on respiratory system, etc. The fruit is considered poisonous when eaten raw, with nausea, vomiting, diarrhea, and abdominal pain as side effects after ingestion. Most traditional uses are supported by biological activities demonstrated in modern experimental studies, suggesting a potential medicinal value of N. domestica. However, more information is needed on its mechanisms of activity, pharmacokinetic profile of the constituents, and its safety and efficacy profile in humans.